2020
DOI: 10.3390/app10175776
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Artificial Neural Network Models for Water Quality Prediction

Abstract: Water quality prediction plays an important role in environmental monitoring, ecosystem sustainability, and aquaculture. Traditional prediction methods cannot capture the nonlinear and non-stationarity of water quality well. In recent years, the rapid development of artificial neural networks (ANNs) has made them a hotspot in water quality prediction. We have conducted extensive investigation and analysis on ANN-based water quality prediction from three aspects, namely feedforward, recurrent, and hybrid archit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
136
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(145 citation statements)
references
References 174 publications
(290 reference statements)
0
136
0
9
Order By: Relevance
“…Finally, all samples were randomly divided into three groups: training (50%), validation (17%), and test (33%). The validation dataset was used as an intermediate dataset for the fine tuning of the utilized classifiers [28].…”
Section: Reference Datamentioning
confidence: 99%
“…Finally, all samples were randomly divided into three groups: training (50%), validation (17%), and test (33%). The validation dataset was used as an intermediate dataset for the fine tuning of the utilized classifiers [28].…”
Section: Reference Datamentioning
confidence: 99%
“…An artificial neural network (ANN) is a computing system animated by studies of the brain and nervous system [ 37 ] as in the human brain [ 18 ]. ANN carries out perfect mathematical complex systems and is based on a system of interconnected “neurons” [ 36 , 48 , 58 ] forming the basis of neural network operation. The network has computational models that are defined by four parameters: (i) processing elements known as neurons, (ii) a topology comprising weighted connections between neurons, (iii) a learning algorithm for training the network, (iv) a recall algorithm for testing or classifying purposes [ 59 ].…”
Section: Theoretical Foundations and Application In Water Quality Predictionmentioning
confidence: 99%
“…Moreover, the models are less sensitive to data insufficiency; the structures are flexible, non-linear, and robust, and can handle vast amounts of data and data at different scales [ 60 , 61 , 62 , 63 , 64 , 65 ]. As a result, many researchers have explored artificial neural networks (ANN), multilayer perceptron (MLP) and feed-forward neural networks (FFNN) [ 40 , 66 , 67 , 68 ], to predict; forecast, and model future water quality in groundwater [ 2 , 48 ], surface water [ 1 , 6 , 7 , 9 , 31 , 33 , 40 , 42 , 58 , 67 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ], and wastewater treatment plants [ 68 , 76 ]. A review on water quality prediction by [ 58 ] for a period 2008–2019 concluded that the MLP architecture in ANN was the widely used architecture to complete prediction tasks during this period.…”
Section: Theoretical Foundations and Application In Water Quality Predictionmentioning
confidence: 99%
See 2 more Smart Citations